Competition Strategy in the Islamic Banking Industry: An Empirical Review - Rahmayati Rahmayati (Research Collaboration Community (RCC), 2021)
The research purpose to understand about Islamic banking industry competition in the marketing. The research method is used in the form of library research which collecting data by using written materials. The competition demands Islamic banking to be more aggressive than before to apply marketing strategic especially during Covid-19 pandemic. The government give recommendation and instruction that Islamic banking is demanded to serve customer by digitization of bank service. Islamic banking can reach a wider market. Acceleration of technology driven business model has to be a main priority during and pasca Covid-19 pandemic. The study found that the competition strategy in the Islamic banking Industry adopted by the marketing value is having a significant impact on to serve customer by digitization of bank service.